SKEPTISISME DALAM HERMENEUTIKA FEMINIS FATIMA MERNISSI - Aulassyahied, Qaem (IAIN Pekalongan, 2016)
This paper explores the Fatima Mernissi of Hermeneutics with Feminism paradigm. According to him, one of the sources of discrimination against women is the interpretation the clerics of the some hadith that are full of with a view of masculinity. Fatima Mernissi does not hesitate to mention the narrators on Thabaqat companions, like Abu Hurariah which has narrated some hadith recognition of the Prophet, however full of with interests that lead to hatred against women. Skepticism and excessive criticism, of Fatima Mernissi was found when there is no recognition that false hadiths, can occur because of a mistake narrators without the element of intent. The attitude of skepticism Fatima Mernissi also found when, citing the data source from the book of scholars by adding a few words which caused it means to be biased, and also a negative view of the narrations that are considered misogynistic.Tulisan ini mengeksplorasi Hermeneutika Fatima Mernissi dengan paradigma Feminisme. Menurutnya, salah satu sumber diskriminasi terhadap perempuan adalah tafsiran para ulama terhadap beberapa hadis yang sarat dengan pandangan maskulinitas. Fatima Mernissi tidak segan menyebutkan perawi pada Thabaqat sahabat, seperti Abu Hurariah yang telah meriwayatkan beberapa hadis yang diakuinya dari Rasulullah namun sarat kepentingan dan tendensius yang mengarah kepada “anti perempuan”. Sikap skeptis dan kritik berlebihan yang dilakukan oleh Fatima Mernissi ditemukan ketika tidak ada pengakuan bahwa hadis palsu dapat terjadi karena kekeliruan perawi tanpa adanya unsur kesengajaan. Sikap skeptisisme Fatima Mernissi juga ditemukan ketika mengutip sumber data dari kitab ulama dengan menyusupkan beberapa kata yang menyebabkan maknanya menjadi bias dan memandang negatifriwayat-riwayat yang dianggap misoginis.